2020
DOI: 10.1155/2020/6837982
|View full text |Cite
|
Sign up to set email alerts
|

Kaji-Ichigoside F1 and Rosamultin Protect Vascular Endothelial Cells against Hypoxia-Induced Apoptosis via the PI3K/AKT or ERK1/2 Signaling Pathway

Abstract: As a pair of differential isomers, Kaji-ichigoside F1 and Rosamultin are both pentacyclic triterpenoids isolated from the subterranean root of Potentilla anserina L., a plant used in folk medicine in western China as antihypoxia and anti-inflammatory treatments. We demonstrated that Kaji-ichigoside F1 and Rosamultin effectively prevented hypoxia-induced apoptosis in vascular endothelial cells. We established a hypoxia model, using EA.hy926 cells, to further explore the mechanisms. Hypoxia promoted the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Oxidative stress deepens the understanding of the cellular senescence process and provides promising tools for the development of new therapeutic strategies [ 31 ]. Rosa roxburghii is a natural medicinal and edible plant that is unique to the mountainous area of southwest China, in which its main active ingredients are flavonoid of Rosa roxburghii Tratt and triterpenoids of Rosa roxburghii Tratt , and has antioxidant and antihypoxia effects [ 29 , 30 ]. Recent study has shown that Rosa roxburghii can attenuate arsenic poisoning by regulating element balance and oxidative stress [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress deepens the understanding of the cellular senescence process and provides promising tools for the development of new therapeutic strategies [ 31 ]. Rosa roxburghii is a natural medicinal and edible plant that is unique to the mountainous area of southwest China, in which its main active ingredients are flavonoid of Rosa roxburghii Tratt and triterpenoids of Rosa roxburghii Tratt , and has antioxidant and antihypoxia effects [ 29 , 30 ]. Recent study has shown that Rosa roxburghii can attenuate arsenic poisoning by regulating element balance and oxidative stress [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very limited effective targeted prevention and treatment measures for skin cell senescence caused by arsenic. Rosa roxburghii is a natural medicinal and edible plant that is unique to the mountainous area of southwest China and has antioxidant and antihypoxia effects [ 29 , 30 ]. Its main active ingredients include polysaccharides, flavonoids, superoxide dismutase, vitamin C, and triterpenes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies ( Chen et al, 2007 ; Mahata et al, 2008 ; Zablotska et al, 2008 ; Xu et al, 2016 ; Xia et al, 2020 ; Xu et al, 2021b ) have shown that vitamins, trace elements, and natural medicinal plants can be used to prevent and treat endemic arsenism. RRT , a traditional Chinese health food that is unique to the mountainous area of southwest China ( An et al, 2011 ; Shi et al, 2020 ), contains a variety of biologically active metabolites (such as pentacyclic triterpenoids and flavonoids) and rich nutrients (including trace elements, vitamins, polysaccharides, dietary fiber, unsaturated fatty acids, and superoxide dismutase) ( Wu et al, 2020 ). Our previous animal study found that RRT can attenuate liver damage in arsenic-poisoned rats by regulating element balance and oxidative stress ( Xu et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Natural medicinal and edible plants have contributed extensively towards the development of modern medicine ( Kushiro et al, 2003 ); however, a large number of natural products are yet to be developed and applied ( Sen and Samanta, 2015 ). Rosa roxburghii Tratt ( RRT ) juice is the original juice of Rosa roxburghii Tratt fruit, which is a traditional Chinese health food that is unique to the mountainous area of southwest China ( Shi et al, 2020 ). RRT contains a variety of biologically active metabolites (such as pentacyclic triterpenoids and flavonoids) and rich nutrients (including trace elements, vitamins, polysaccharides, dietary fiber, unsaturated fatty acids, and superoxide dismutase) ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AKT refers to a downstream effector of phosphoinositide 3-kinase (PI3K); therefore, PI3K/AKT represents a critical pathway of cellular processes that are responsible for cell survival [ 13 , 14 ]. A study indicated that the activation of PI3K/AKT signaling inhibited hypoxia-induced apoptosis in vascular endothelial cells [ 15 ]. Apart from that, the PI3K/AKT pathway was related to the apoptosis of cardiomyocytes subjected to ischemic hypoxia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%